Implementation of unassisted and community-based HIV Self-Testing (HIVST) during the COVID-19 pandemic among Men-who-have-sex-with-Men (MSM) and Transgender Women (TGW): A demonstration study in Metro Manila, Philippines - John Danvic T. Rosadiño; Ronivin G. Pagtakhan; Matthew T. Briñes; Jeanno Lorenz G. Dinglasan; Denis P. Cruz; John Oliver L. Corciega; Aeronne B. Pagtakhan; Zypher Jude G. Regencia; Emmanuel S. Baja (PLoS ONE, 2023)
Objective The study aimed to demonstrate the feasibility of an unassisted and community-based HIV self-testing (HIVST) distribution model and to evaluate its acceptability among men-having-sex-with-men (MSM) and transgender women (TGW). Methods Our demonstration study focused on implementing the HIVST distribution model in Metro Manila, Philippines. Convenience sampling was done with the following inclusion criteria: MSM or TGW, at least 18 years old, and had no previous HIV diagnosis. Individuals taking HIV pre-exposure prophylaxis, on antiretroviral therapy, or female sex at birth were excluded. The implementation of the study was done online using a virtual assistant and a delivery system via courier due to COVID-19-related lockdowns. Feasibility was measured by the number of HIVST kits successfully delivered and utilized and the HIV point prevalence. Moreover, acceptability was evaluated by a 10-item system usability scale (SUS). HIV prevalence was estimated with linkage to care prioritized for reactive participants. Results Out of 1,690 kits distributed, only 953 (56.4%) participants reported their results. Overall, HIV point prevalence was 9.8%, with 56 (60.2%) reactive participants linked to further testing. Furthermore, 261 (27.4%) of respondents self-reported, and 35 (13.4%) of the reactive participants were first-time testers. The HIVST service had an overall median and interquartile range (IQR) SUS score of 82.5 (IQR: 75.0, 90.0), rendering the HIVST kits very acceptable. Conclusions Our study suggests the acceptability and feasibility of HIVST among the MSM and TGW in Metro Manila, Philippines, regardless of their age or HIV testing experience. In addition, other platforms of information dissemination and service delivery of HIVST should be explored, including access to online instructional videos and printed materials, which may facilitate easier use and interpretation of results. Furthermore, due to our study’s limited number of TGW respondents, a more targeted implementation strategy to reach the TGW population is warranted to increase their access and uptake of HIVST.